L’Aventure olympique. Les architectures des Jeux d’hiver d’Albertville 1992 : des projets inaboutis ? - Marie Beauvalet-Boutouyrie (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Olympic architectures, because of their complexity, constitute a privileged case study for project failures and unrealizations. At the 1992 Albertville Olympic Games, political, economic, and territorial issues took precedence over architectural matters. Although this event was a real opportunity to create striking and well-designed architecture, this possibility seems to have been « neglected » since the original Olympic bid. It seems as though some of the projects have been mishandled, resulting in sometimes mangled and often forgotten Olympic architectures. The role of the organizing committee of the Games as well as that of the municipalities hosting the event is to be examined. It remains to be seen whether a lack of initial consideration of architecture or through questionable decisions on the part of the project management are to be « blamed ». The example of the pièce de resistance that is the Albertville’s Halle de Glace is, for this reason, the most telling and worthy of investigation.